THE IMPLICATURE IN DILAN 1990, A NOVEL BY PIDI BAIQ - Faradilla Mayanksari; Inok Tri Puji Rahayu (Dinamika Bahasa dan Budaya, 2017)
A dialogue or conversation is an important thing in the most of literary work. Authors use them to tell or illustrate their work. Especially is in the novel or short story. A dialogue or conversation can make the reader understand their work well. Every author has their characteristic on their writing. But most of them are always use one or some of the type of pragmatics. One of the type of pragmatic that usually used by an author is implicature. Like as in the DILAN 1990 novel by Paid Baiq, some conversations are use implicature to deliver an implicit meaning. There are some dialogues which delivered by some characters have hidden meaning. And sometimes, it will make the readers will think twice to understand what is the meaning of that sentence. Implicature is the approach which uses to explain some hidden meaning in the dialogue or narration of DILAN 1990 novel. This research focuses on the maxim of the dialogue and narration toward this novel to examine some hidden meaning that include in some part. This research use descriptive qualitative method and results the forms of implicature. They are maxim of relevant, quality, quantity and manner that used in the DILAN 1990 novel.Keywords: dialogue, novel, implicature, hidden meaning, maxim